Um estudo das potencialidades pedagógicas de atividades exploratórias-investigativas com o material didático geoespaço - Kusuki, Luiz Rodolfo (2014)
This research has as its context the exploration potential of manipulative materials in mathematics teaching Geoespaço. In order to increase knowledge of the development and implementation of exploratory-investigative tasks and tasks of figural representation involving manipulative materials Geoespaço and having specific objectives the development and use of Geoespaço in different didactic sequences. The theoretical foundation takes the qualitative and quantitative analysis Proceedings of the National Meetings of Mathematics Education (ENEMs) from 2001 to 2010 and the Proceedings of the National Association of Postgraduate Education and Research (Anped) from 2000 to 2013, more specifically, on the use of manipulative materials from of Lorenzato (2006) and Bezerra (1962), on the theory of figural representations of Fischbein (1993) and on the exploratory-investigative tasks Bridge (2009). The relevance of this research is partly because of making clear the importance of making use of manipulative materials in exploratory-investigative tasks in various methodologies of teaching math.